GIS: A USEFUL TOOL FOR MANAGING OF TRANSBOUNDARY AQUIFERS: A CASE STUDY FROM PRESPA LAKE BASIN - Kiri, E. (Bulletin of the Geological Society of Greece, 2016)
Prespa Lake Basin is a transboundary basin that’s shared between Albania-Greece-FYROM. This region has a very complicated geology. The main aquifer systems are developed in carbonate rocks (karst aquifers) crossing international borders (transboundary aquifers). A map was constructed in GIS environment clearly display that each geologic age has one index, in one polygon, with the respective geological formation. The map was first digitalized with an AutoCAD program and then all the layers were exported in the program mentioned above. Not only does this map represent the hydrogeological features of the area but it also serves as a database of general characteristics, such as, the rock type, the infiltration coefficient, the yield of wells and springs, groundwater resource and permeability can be found on this base. Furthermore, chemical data can be added to the map, supplying more information on the surface and groundwater. Geographical Information Systems (GIS) is a useful tool for water resources management in the frame of international cooperation and coordination.